2020
DOI: 10.1186/s12886-020-01547-1
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological outcomes of unilateral coronal synostosis in young children

Abstract: Background: To report refractive outcomes, describe types of strabismus and evaluate the outcomes of surgical intervention for unilateral coronal synostosis (UCS) in paediatric patients. Methods: This study retrospectively included 30 UCS cases. Patients aged from 3 months to 6 years (median: 1.8 years) were enrolled from January 2018 to December 2019 at Shanghai Children's Hospital. Sixteen patients had all types of strabismus; 15 of these patients underwent surgery. Results: Refractive errors of 30 cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…Ophthalmologic defects and visual abnormalities have been well described in association with craniosynostosis. [24][25][26][27] Astigmatism has been reported as the most common comorbid ophthalmologic conditions in patients with UCS in prior studies, [24][25][26][27] a finding that was also demonstrated in the present cohort (Table 3). In addition, the present study showed that conditions involving aberrant CNs (eg, hyperopia and trochlear nerve palsy) were more frequently involved on the synostotic side.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Ophthalmologic defects and visual abnormalities have been well described in association with craniosynostosis. [24][25][26][27] Astigmatism has been reported as the most common comorbid ophthalmologic conditions in patients with UCS in prior studies, [24][25][26][27] a finding that was also demonstrated in the present cohort (Table 3). In addition, the present study showed that conditions involving aberrant CNs (eg, hyperopia and trochlear nerve palsy) were more frequently involved on the synostotic side.…”
Section: Discussionsupporting
confidence: 85%
“…Ophthalmologic defects and visual abnormalities have been well described in association with craniosynostosis 24–27 . Astigmatism has been reported as the most common comorbid ophthalmologic conditions in patients with UCS in prior studies, 24–27 a finding that was also demonstrated in the present cohort (Table 3).…”
Section: Discussionsupporting
confidence: 79%
“…Refractive errors and anisometropia are more common, certainly in unicoronal synostosis where it is postulated to be due to oblique astigmatism caused by changes in the corneal curvature as a result of the anatomical deformation in this condition. [ 13 14 15 ] It is however also more common in syndromic synostosis and does not appear to be impacted upon by craniofacial surgery. All children attending ophthalmic department should be refracted, with increased likelihood of glasses wear in those with coronal synostosis.…”
Section: A Nisometropiamentioning
confidence: 99%
“…Particular attention was necessary for the reconstruction of both superior oblique muscles pulleys because these are areas of interest in oculomotor disorders found in anterior plagiocephaly. 7,12 The optic nerves and the anterior segment of both eyeballs were not modelized as they were assumed to play a negligible role in strains and displacements studied. Then, the meshing was produced using Hypermesh software (Altair Engineering, Inc., Detroit, MI).…”
Section: Model Descriptionmentioning
confidence: 99%
“…This involvement of the both trochlear areas in regards of the pulleys of the superior oblique muscles, is interesting because V-pattern strabismus with hypofunction of the superior oblique muscle is often described in patient with anterior plagiocephaly. 12,16,17 The presence of strain on the insertion of the pulley of the superior oblique muscle may be a contributing factor for the V-pattern strabismus. It would be necessary to evaluate the evolution of this area of strain during the postoperative period.…”
Section: Orbital Bonementioning
confidence: 99%